Dormancy release of Norway spruce under climatic warming: testing ecophysiological models of bud burst with a whole-tree chamber experiment - Hänninen, Heikki; Slaney, Michelle; Linder, Sune (Tree Physiology, 2007)
Ecophysiological models predicting timing of bud burst were tested with data gathered from 40-year-old Norway spruce ( Picea abies (L.) Karst.) trees growing in northern Sweden in whole-tree chambers under climatic conditions predicted to prevail in 2100. Norway spruce trees, with heights between 5 and 7 m, were enclosed in individual chambers that provided a factorial combination of ambient (365μmol mol−1) or elevated (700μmol mol−1) atmospheric CO 2 concentration, [CO 2 ], and ambient or elevated air temperature. Temperature elevation above ambient ranged from +2.8 °C in summer to +5.6 °C in winter. Compared with control trees, elevated air temperature hastened bud burst by 2 to 3 weeks, whereas elevated [CO 2 ] had no effect on the timing of bud burst. A simple model based on the assumption that bud rest completion takes place on a fixed calendar day predicted timing of bud burst more accurately than two more complicated models in which bud rest completion is caused by accumulated chilling. Together with some recent studies, the results suggest that, in adult trees, some additional environmental cues besides chilling are required for bud rest completion. Although it appears that these additional factors will protect trees under predicted climatic warming conditions, increased risk of frost damage associated with earlier bud burst cannot be ruled out. Inconsistent and partially anomalous results obtained in the model fitting show that, in addition to phenological data gathered under field conditions, more specific data from growth chamber and greenhouse experiments are needed for further development and testing of the models.